Development of the estimating methodology of a 5TDF engine motor resource consumption under different operating modes of the machine - Makogon, Helen; Sirosh, Vitaliy; Guba, Serhiy; Lavrut, Oleksandr; Zagrebelnuy, Sergiy; Rudiy, Andriy (Національний технічний університет "Харківський політехнічний інститут", 2022)
The subject matter of the article is accounting for the motor resource of the 5TDF tank engine under different operating modes. The goal of the study is to development of a methodology for estimating the consumption of a motor resource of a 5TDF engine under different operating modes of the machine. The tasks to be solved are: based on the analysis of data on the operating modes of the 5TDF engine, to determine a set of parameters that give empirical and analytical estimates of the consumption of the motor resource of the machine; to request analytical estimates of the consumption of the 5TDF engine motor resource in terms of the number of years' service in different machine operating modes; to propose a mechanism for the processing of numerical values, depending on the results of the statistical processing of these machine operation data. General scientific and special methods of scientific knowledge are used. The following results were obtained: A continuous functional dependence of the actual number of hours spent by the engine on the values of the meter per hours at different speeds, allow more careful accounting of engine consumption, but will involve the development of special devices based on modern elements has been determined.

Предметом вивчення в статті є облік моторесурсу двигуна танка 5ТДФ на різних режимах роботи. Метою статті є розробка методики оцінки витрат моторесурсу двигуна 5ТДФ при різних режимах експлуатації машини. Завдання дослідження: на основі аналізу даних про режими роботи двигуна 5ТДФ визначити безліч параметрів, що дають емпіричні та аналітичні оцінки витрат моторесурсу машини; запропонувати аналітичні оцінки витрат моторесурсу двигуна 5ТДФ від кількості відпрацьованих мотогодин при різних режимах експлуатації машини; запропонувати механізм розрахунку числових значень, виходячи з результатів їх статистичної обробки даних експлуатації машини; проаналізувати конструктивні можливості практичної реалізації розробленої методики з огляду на наявні контрольно-вимірювальні прилади, встановлені на зразку Т-64Б. Методологічною основою дослідження стали загальнонаукові та спеціальні методи наукового пізнання. Отримані наступні результати: Визначена безперервна функціональна залежність фактичної кількості годин роботи двигуна від значень лічильника за годину на різних швидкостях, що дозволить більш ретельно вести облік витрати двигуна, але передбачатиме розробку спеціальних приладів на основі сучасної елементної бази.
Розробка методики оцінки витрати моторесурсу двигуна 5ТДФ за різних режимах роботи машини
Keywords: consumption of motor resource of the 5TDF engine; regression equation; least squares method; accounting for tank hours counters; витрата моторесурсу двигуна 5ТДФ; рівняння регресії; метод найменших квадратів; облік показників лічильника мотогодин в танку